2020
DOI: 10.1055/s-0040-1710514
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Onyx Embolization of Carotid-Cavernous Fistulas: Mid- and Long-Term Outcomes

Abstract: Objective Endovascular treatment of carotid-cavernous fistulas (CCFs) has been consistently shown to give excellent results and is currently the mainstay of treatment of these complex vascular pathologies. Onyx is currently the most widely used agent, but there has been concern over high rates of cranial nerve (CN) deficits seen in patients with CCF treated with Onyx and paucity of data on long-term outcomes. Methods This is a retrospective analysis of patients who underwent transvenous Onyx emboliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…Cerebral angiography is the gold standard for definitive diagnosis, classification and therapeutic planning [ 1 ]. Recent advances in endovascular technology have expanded the range of treatment options for CCFs and favorable long-term outcomes have been achieved [ 2 4 ]. As a result, the mainstay of treatment for CCFs consists of transarterial or transvenous embolization.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral angiography is the gold standard for definitive diagnosis, classification and therapeutic planning [ 1 ]. Recent advances in endovascular technology have expanded the range of treatment options for CCFs and favorable long-term outcomes have been achieved [ 2 4 ]. As a result, the mainstay of treatment for CCFs consists of transarterial or transvenous embolization.…”
Section: Introductionmentioning
confidence: 99%
“…The complication rate of EVT ranged between 2.3% and 53.3% across different studies. [2][3][4][5]13,15,24,25 In a systemic review and meta-analysis of 21 studies, Alexandre et al 15 found a complication rate of 7.8%. In our series, 23% of patients experienced different complications following EVT, which was more common following LEAs than coiling alone (32% vs 15%).…”
Section: Discussionmentioning
confidence: 99%
“…Ocular symptoms generally improved in 60%-100% of patients following EVT. 2,3,12,13,17,24 While proptosis, chemosis, and tinnitus could rapidly disappear following embolization, CN palsy and vision deficits take several months to improve. 29 In our series, 31% of patients showed immediate improvement of the ocular symptoms after EVT, which was more common following coiling alone (42.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported variable occlusion rates across the literature. [14][15][16][17] Beer-Furlan et al demonstrated a 100% complete occlusion rate following TV Onyx embolization of 3 direct and 4 indirect CCFs. 14 Suzuki et al treated 6 spontaneous CCFs transvenously using a combination of coils and Onyx with an immediate complete occlusion rate of 66.7%.…”
Section: Ta Approachmentioning
confidence: 99%
“…[14][15][16][17] Beer-Furlan et al demonstrated a 100% complete occlusion rate following TV Onyx embolization of 3 direct and 4 indirect CCFs. 14 Suzuki et al treated 6 spontaneous CCFs transvenously using a combination of coils and Onyx with an immediate complete occlusion rate of 66.7%. 16 Recurrence was seen in 2 cases and required a second treatment.…”
Section: Ta Approachmentioning
confidence: 99%